2021
DOI: 10.1016/j.resuscitation.2021.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral perfusion and metabolism with mean arterial pressure 90 vs. 60 mmHg in a porcine post cardiac arrest model with and without targeted temperature management

Abstract: Aim: To determine whether targeting a mean arterial pressure of 90 mmHg (MAP90) would yield improved cerebral blood flow and less ischaemia compared to MAP 60 mmHg (MAP60) with and without targeted temperature management at 33 C (TTM33) in a porcine post-cardiac arrest model. Methods: After 10 min of cardiac arrest, 41 swine of either sex were resuscitated until return of spontaneous circulation (ROSC). They were randomised to TTM33 or no-TTM, and MAP60 or MAP90; yielding four groups. Temperatures were managed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
(28 reference statements)
2
6
1
Order By: Relevance
“…The effects of inapt BP are more likely to be felt to a greater extent in the brain, which can lead to detrimental consequences ( 27 ). The 24-h postoperative MAP in this study was 89.9 mmHg, which is similar to the MAP target recommended by previous animal studies, clinical studies, and meta-analyses ( 28 30 ). However, the optimal mean MAP was not associated with favorable outcomes in our study.…”
Section: Discussionsupporting
confidence: 89%
“…The effects of inapt BP are more likely to be felt to a greater extent in the brain, which can lead to detrimental consequences ( 27 ). The 24-h postoperative MAP in this study was 89.9 mmHg, which is similar to the MAP target recommended by previous animal studies, clinical studies, and meta-analyses ( 28 30 ). However, the optimal mean MAP was not associated with favorable outcomes in our study.…”
Section: Discussionsupporting
confidence: 89%
“…In a recent study of pigs, increasing MAP to 90 mmHg (compared to 60 mmHg) resulted in increased cerebral blood flow. 17 We did, however, not find increased NIRS with increasing MAP, which may be due to limitations with NIRS as a reflection of cerebral blood flow. Another study by Jakkula et al, found no association between NIRS-values and biomarkers of brain injury in patients resuscitated from OHCA.…”
Section: Discussioncontrasting
confidence: 63%
“…The lower limit of cerebral autoregulation might become higher in post-resuscitated patients [9]. Targeting higher blood pressure (BP) might theoretically improve cerebral blood perfusion and neurologic outcomes [10]. However, current evidence is not conclusive, and several observational studies have reported controversial results [6,[11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%